Model Sistem Dinamik Stok Beras untuk Mendukung Ketahanan Pangan Provinsi Bali - I Gede Yudi Pradnyana; I Wayan Widia; Sumiyati Sumiyati (Program Studi Teknik Pertanian dan Biosistem, Fakultas Teknologi Pertanian, Universitas Udayana, Badung, Bali, Indonesia, 2021)
Limited rice production capacity and increased rice consumption make food insecurity conditions in terms of insufficient rice stocks inevitable. The complexity of rice problems in Bali is not only related to fulfillment for local people but also for tourists. This study aims to analyze the dynamics of the causal-loop relationship of variables that affect the state of production, consumption, and rice stock in the Bali Province using a systems approach and the application of dynamic system modeling techniques. In this study the Causal-Loop Diagram (CLD) of the rice stock system is formulated on the basis of the interrelationship of the production sub-system, the consumption sub-system and the government rice reserve sub-system which involves the relationship of 24 variables to produce a model output that is the projected rice stock in Bali for the period of 2021-2030. Validation of the simulation results against the actual data in the model using the RMSPE method shows a value of 4,7062 percent (<5 percent), this means that the model is said to be very valid. Model simulation results based on existing conditions (scenario 0), show that rice stocks begin to decline since 2018 with an average decline rate of 19,76 percent/year. The rice stock deficit begin in 2026 at 36.458 tons and continue in 2030 at 448.162 tons. This condition can be overcome if the provincial government of Bali implements an effective policy with a policy option that is to increase productivity of rice yields with a minimum target of 6,7148 ton/hectare (scenario 1 optimistic) and or an increase in cropping intensity with a minimum target of 2,0622 (scenario 3 optimistic).